Fiscal Policy for Inclusive Growth: An Overview - Gemma Estrada; Sang-Hyop Lee; Donghyun Park (Asian Development Bank (ADB), 2014)
In recent years, inequality has risen in the region alongside rapid economic growth. The widening income gap strengthens the case for a government response, and fiscal policy is one of the most suitable policy instruments to promote a more equitable society that provides opportunities for all. Developing Asia has trailed other parts of the world in equity-promoting fiscal expenditures, namely education, health care, and social protection, and thus the region needs to do more. Expanding public expenditures without boosting fiscal resources can, however, jeopardize fiscal sustainability. The key challenge is how to use fiscal policy to make growth more inclusive while maintaining fiscal sustainability.
hdl:11540/4218
Keywords: D31; H20; H50; 330; fiscal policy; inclusive growth; Asia; economic growth; equity; Finanzpolitik; Wirtschaftswachstum; Verteilungsgerechtigkeit; Asien